Multi-scale Dynamical Processes in Space and Astrophysical Plasmas - Leubner, Manfred P.; Vörös, Zoltán; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Magnetized plasmas in the universe exhibit complex dynamical behavior over a huge range of scales. The fundamental mechanisms of energy transport, redistribution and conversion occur at multiple scales. The driving mechanisms often include energy accumulation, free-energy-excited relaxation processes, dissipation and self-organization. The plasma processes associated with energy conversion, transport and self-organization, such as magnetic reconnection, instabilities, linear and nonlinear waves, wave-particle interactions, dynamo processes, turbulence, heating, diffusion and convection represent fundamental physical effects. They demonstrate similar dynamical behavior in near-Earth space, on the Sun, in the heliosphere and in astrophysical environments. 'Multi-scale Dynamical Processes in Space and Astrophysical Plasmas' presents the proceedings of the International Astrophysics Forum Alpbach 2011. The contributions discuss the latest advances in the exploration of dynamical behavior in space plasmas environments, including comprehensive approaches to theoretical, experimental and numerical aspects. The book will appeal to researchers and students in the fields of physics, space and astrophysics, solar physics, geophysics and planetary science.  .
Part I Magnetic field topology and reconnection -- Field Line Topology and Rapid Reconnection -- Acceleration of Energetic Particles through Reconnection of Weakly Stochastic Magnetic Field -- Dynamical Behaviors of the Solar Chromosphere Observed with Hinode Dynamics in Sunspot Light Bridges and Magnetic Reconnection Processes -- Signatures of magnetic reconnection in solar eruptive flares: A multi-wavelength perspective -- Energy Cascades in Large-scale Solar Flare Reconnection -- Plasmoids in Solar Flares and their Radio and X-ray Signatures -- Occurrence of Magnetic Reconnection in the Deep Magnetotail: ARTEMIS Results -- Part II Plasma relaxation and heating -- Relaxation and heating triggered by nonlinear kink instability: application to solar flares and coronal heating -- Plasma Relaxation in Hall Magnetohydrodynamics -- Alfvén Waves in Dusty Proto-Stellar Accretion Disks -- Part III Statistical physics and entropy approaches -- Turbulent equilibrium and nonextensive entropy -- Modeling space plasma dynamics with anisotropic Kappa distributions -- Part IV Waves, shocks and turbulence -- MagnetohydrodynamicWaves in Partially Ionized Prominence Plasmas -- Alfvén Amplifier in the Solar Atmosphere -- Alfvénic Solitary and Shock Waves in Plasmas -- Recent Progress in the Theory of Electron Injection in Collisionless Shocks -- Superdiffusive transport at shocks in space plasmas -- Inversion of physical parameters in solar atmospheric seismology -- Interaction of wave packets in MHD and EMHD turbulence -- Observations of Electromagnetic Fluctuations at Ion Kinetic Scales in the Solar Wind -- On the passive nature of proton temperature in solar wind turbulence -- Part V Heliogeophysics and planetary physics -- Fine Particles and Nonlinear Processes in Plasma Heliogeophysics -- Magnetospheres of the Mercury, Earth, Jupiter, and Saturn -- Location of the inner edges of astrophysical discs related to the central object -- Stochastic properties of solar activity proxies.
Keywords: Space sciences; Astrophysics; Space Sciences (including Extraterrestrial Physics, Space Exploration and Astronautics).; Astrophysics and Astroparticles